Compound oil well cement fluid loss agent and preparation method thereof

By combining compound oil well cement fluid loss control agents, the problem of reduced effectiveness of traditional cement fluid loss control agents under high temperature and high salinity conditions has been solved, achieving higher water resistance and salt resistance, making it suitable for cementing operations in high temperature and high salinity environments.

CN119285272APending Publication Date: 2025-01-10SICHUAN CHUANQING UNDERGROUND TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411184489.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Traditional oil well cement fluid loss control agents show a significant decrease in effectiveness under high temperature and high salinity conditions, leading to increased water loss in cement slurry and affecting cementing quality and wellbore stability.

Method used

A compound oil well cement fluid loss reducer is adopted, which is composed of temperature and salt resistant polymer, sulfonated styrene copolymer, high temperature resistant liquid fluid loss reducer and silane coupling agent KH-560. Through the blending of modified silica and styrene copolymer, a compound fluid loss reducer with excellent dispersing, scale inhibition and water reduction properties is formed.

Benefits of technology

It improves the water resistance, erosion resistance and salt resistance of fluid loss control agents, expands the scope of application, meets the needs of use in high temperature and high salt environments, and ensures cementing quality and construction safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005013138570000111
    Figure BDA0005013138570000111
Patent Text Reader

Abstract

The invention relates to the technical field of oil well operation admixtures, in particular to a compound oil well cement fluid loss agent and a preparation method thereof. The sulfonated styrene copolymer prepared by taking styrene, maleic anhydride and benzoyl peroxide as raw materials and the high-temperature-resistant liquid fluid loss agent prepared by taking itaconic acid, acrylamide and 2-acrylamido-2-methylpropanesulfonic acid as raw materials are blended, so that the effects of improving the comprehensive performance and expanding the application range are achieved; the sulfonated styrene copolymer has excellent dispersion, scale inhibition and water reduction performance, the high-temperature-resistant liquid fluid loss agent has excellent high-temperature resistance and water loss reduction performance, after the sulfonated styrene copolymer and the high-temperature-resistant liquid fluid loss agent are blended, the advantages of the sulfonated styrene copolymer and the high-temperature-resistant liquid fluid loss agent can be integrated, and the composite fluid loss agent with more comprehensive and excellent performance is formed. The fluid loss agent prepared by blending is matched with the temperature-resistant and salt-resistant polymer, so that the respective advantages of the three raw materials can be fully utilized, the waste of the raw materials is reduced, and the saving and efficient utilization of resources are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oil well operation admixtures, and in particular to a compound oil well cement fluid loss reducer and a preparation method thereof. Background Art

[0002] In the field of oil exploration and development, oil well cementing operations are a key link to ensure the long-term stable production of oil and gas wells. However, as oil and gas resource exploitation gradually extends to extreme environments such as deep sea, high temperature, high pressure and high salinity, traditional oil well cement fluid loss reducers face huge challenges. Especially under high temperature and high salinity conditions, the efficiency of fluid loss reducers decreases significantly, resulting in increased water loss in cement slurry, which in turn affects cementing quality and wellbore stability.

[0003] In high temperature, high pressure and high mineralization environment, traditional cement slurry additives often fail to meet the requirements and ensure cementing quality and construction safety. Therefore, developing an oil well cement fluid loss reducer with high salt resistance and high temperature resistance is of great significance to ensure the safe and efficient development of oil and gas fields. Summary of the invention

[0004] Technical issues solved

[0005] In view of the above-mentioned shortcomings of the prior art, the present invention provides a composite oil well cement fluid loss reducer and a preparation method thereof, which can effectively solve the problem of poor salt resistance and temperature resistance of the fluid loss reducer in the prior art.

[0006] Technical Solution

[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0008] A composite oil well cement fluid loss reducer, the composite oil well cement fluid loss reducer is composed of the following components: a temperature-resistant and salt-resistant polymer, a sulfonated styrene copolymer, a high temperature-resistant liquid fluid loss reducer and a silane coupling agent KH-560;

[0009] The temperature-resistant and salt-resistant polymer is prepared with modified silicon dioxide, acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, maleic anhydride and sodium p-styrenesulfonate as raw materials;

[0010] The sulfonated styrene copolymer is prepared using styrene, maleic anhydride and benzoyl peroxide as raw materials;

[0011] The high temperature resistant liquid fluid loss reducer is prepared from itaconic acid, acrylamide and 2-acrylamido-2-methylpropanesulfonic acid as raw materials.

[0012] Furthermore, the preparation steps of the modified silicon dioxide are:

[0013] Step 2.1, weigh 2 g of silane coupling agent KH-570 and disperse it in 200 mL of 75% ethanol aqueous solution, disperse it ultrasonically at a frequency of 28 kHz for 30 min, then add anhydrous oxalic acid to adjust the pH value to 5, and the result is recorded as a modified solution;

[0014] Step 2.2, add 10g of nano-silica to the modified solution, ultrasonically disperse it at a frequency of 26kHz for 1.5h, and then condense and reflux it at a temperature of 60°C and a speed of 300r / min for 2.5h to obtain a gel product, wash the gel product with anhydrous ethanol for 3-5 times, filter it, and dry it in a 60°C forced air drying oven for 8h to obtain the modified silica.

[0015] Furthermore, the preparation steps of the temperature-resistant and salt-resistant polymer are:

[0016] Step 3.1, weighing calculated amounts of acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, maleic anhydride and sodium p-styrenesulfonate in a molar ratio of 100:15:10:3 to mix the monomer components;

[0017] Step 3.2, weigh 8-10g of the monomer component, pour it into 100mL of deionized water and disperse it evenly, then add sodium hydroxide aqueous solution to adjust the pH value to 7, then add 0.5-1g of modified silica and mix evenly, the result is recorded as the mixture component, weigh 0.05-0.1g of ammonium persulfate and dissolve it in 10mL of deionized water, and the result after it is fully dissolved is recorded as the initiator component;

[0018] Step 3.3, under nitrogen protection, drip the initiator component into the mixture component, then react at 65° C. for 5 hours, and freeze-dry to obtain a temperature-resistant and salt-resistant polymer.

[0019] Furthermore, in step 3.2, the specific operation for uniform dispersion is stirring at a stirring speed of 500 r / min for 10 min, the mass fraction of the sodium hydroxide aqueous solution is 30%, the specific operation for uniform mixing is stirring at a stirring speed of 600 r / min for 10 min, the specific operation for sufficient dissolution is stirring at a stirring speed of 500 r / min for 10 min, and the dripping rate in step 3.3 is 1 drop / s.

[0020] Furthermore, the preparation steps of the sulfonated styrene copolymer are:

[0021] Step 5.1, first mix toluene and acetone in an equal volume ratio and record it as a solvent component, then weigh styrene, maleic anhydride and benzoyl peroxide in a molar ratio of 1:1.2:1 and mix them as a raw material component, weigh 8-10g of the raw material component and disperse it in 100mL of the solvent component, stir it evenly, heat it to 100℃ and react it for 4h, cool it to room temperature and filter out the solvent, and the result is recorded as a copolymer component;

[0022] Step 5.2, disperse the copolymer components in 50 mL of dichloroethane, heat to 25-30°C, and then add 0.2-0.3 g of sulfur trioxide under nitrogen protection. After reacting for 1-2 hours, add sodium hydroxide aqueous solution to adjust the pH value to 7. After separating the organic phase, place the aqueous phase in an oven at 60°C and dry it for 8 hours. Grind it through a 100-mesh sieve to obtain a sulfonated styrene copolymer.

[0023] Furthermore, in step 5.1, the specific operation of stirring uniformly is stirring at a stirring speed of 500 r / min for 8 minutes, and in step 5.2, the dripping rate is 1 drop / s, and the mass fraction of the sodium hydroxide aqueous solution is 20%.

[0024] Furthermore, the preparation steps of the high temperature resistant liquid fluid loss additive are:

[0025] Step 7.1, weigh 4 g of itaconic acid and 20 g of deionized water into a flask, stir in a water bath at 40-50° C. until completely dissolved, then add a calculated amount of acrylamide, 2-acrylamido-2-methylpropanesulfonic acid and 80 g of deionized water, dropwise add sodium hydroxide aqueous solution to adjust the pH value to 9, and the result is recorded as a monomer component, wherein the molar ratio of itaconic acid, acrylamide and 2-acrylamido-2-methylpropanesulfonic acid is 2:1:7;

[0026] Step 7.2, weigh 2g of silicon carbide powder and 2g of silane coupling agent KH-570, add them to the monomer component, stir and react for 15-30min in a water bath at 40-50°C, add 0.5g of ammonium persulfate and continue to react for 6-8h, and the result is a high temperature resistant liquid fluid loss reducer.

[0027] Furthermore, in step 7.1, the specific operation of stirring until complete dissolution is stirring at a stirring speed of 300 r / min for 10 min, the mass fraction of the sodium hydroxide aqueous solution is 30%, and in step 7.2, the stirring speed of the stirring reaction is 500 r / min.

[0028] A preparation method of a composite oil well cement fluid loss reducer, the preparation method comprising:

[0029] 12-15 parts by weight of a heat-resistant and salt-resistant polymer and 10-12 parts by weight of a sulfonated styrene copolymer are weighed and poured into a ball mill for ball milling. After ball milling for 10 minutes, 1-2 parts by weight of a silane coupling agent KH-560 and 15-18 parts by weight of a high-temperature resistant liquid fluid loss additive are added and ball milling is continued for 10 minutes to obtain a composite oil well cement fluid loss additive.

[0030] Beneficial Effects

[0031] The present invention provides a composite oil well cement fluid loss reducer and a preparation method thereof. Compared with the prior art, the present invention has the following beneficial effects:

[0032] 1. The heat-resistant and salt-resistant polymer prepared by the present invention is a water loss reducer with heat-resistant and salt-resistant properties. The silane coupling agent KH-570 forms an organic adsorption layer by chemically bonding with the hydroxyl groups on the surface of silicon dioxide through its hydrolyzed groups, which can improve the dispersibility of silicon dioxide in organic media. In addition, the methacryloxy functional group of the silane coupling agent KH-570 has the ability to react with the organic polymer, thereby enhancing the binding force between silicon dioxide and the polymer matrix, helping to form a more stable structure in the water loss reducer, and improving the water resistance and resistance of the water loss reducer. Secondly, the addition of acrylamide can improve the cross-linking density and strength of the polymer, thereby enhancing the water resistance and anti-scouring ability of the fluid loss reducer. The addition of 2-acrylamido-2-methylpropanesulfonic acid can improve the water solubility and dispersibility of the polymer, which is helpful for the rapid dispersion and uniform distribution of the fluid loss reducer in oilfield water. The addition of maleic anhydride and sodium p-styrene sulfonate can improve the network structure and strength of the polymer, thereby enhancing the water resistance and salt resistance of the fluid loss reducer, and helping the fluid loss reducer to be better dispersed and stably present in oilfield water.

[0033] 2. The present invention blends a sulfonated styrene copolymer prepared from styrene, maleic anhydride and benzoyl peroxide as raw materials with a high-temperature resistant liquid fluid loss agent prepared from itaconic acid, acrylamide and 2-acrylamido-2-methylpropanesulfonic acid as raw materials, which has the effect of improving comprehensive performance and expanding the scope of application; the sulfonated styrene copolymer has excellent dispersibility, scale inhibition and water reduction performance, while the high-temperature resistant liquid fluid loss agent has excellent high temperature resistance and water loss reduction performance. After the two are blended, the advantages of the two can be combined to form a composite fluid loss agent with more comprehensive and excellent performance. Secondly, the sulfonated styrene copolymer is widely used in the fields of petroleum, construction, chemical industry, etc., while the high-temperature resistant liquid fluid loss agent focuses more on the application under high temperature environment. After the two are blended, the scope of application of the composite fluid loss agent will be expanded, and it can meet the use requirements under more complex and extreme conditions; the fluid loss agent prepared by blending is then matched with the temperature-resistant and salt-resistant polymer, which can make full use of the respective advantages of the three raw materials, reduce the waste of raw materials, and realize resource conservation and efficient utilization. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] The present invention will be further described below in conjunction with the embodiments.

[0036] Example 1

[0037] The composite oil well cement fluid loss reducer of the present embodiment is composed of the following components: a temperature-resistant and salt-resistant polymer, a sulfonated styrene copolymer, a high temperature-resistant liquid fluid loss reducer, and a silane coupling agent KH-560.

[0038] The heat-resistant and salt-resistant polymer is prepared from modified silica, acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, maleic anhydride and sodium p-styrenesulfonate;

[0039] Wherein, the preparation steps of modified silicon dioxide are:

[0040] Step 2.1, weigh 2 g of silane coupling agent KH-570 and disperse it in 200 mL of 75% ethanol aqueous solution, disperse it ultrasonically at a frequency of 28 kHz for 30 min, then add anhydrous oxalic acid to adjust the pH value to 5, and the result is recorded as a modified solution;

[0041] Step 2.2, add 10g of nano-silica to the modified solution, ultrasonically disperse it at a frequency of 26kHz for 1.5h, and then condense and reflux it at a temperature of 60°C and a speed of 300r / min for 2.5h to obtain a gel product, wash the gel product three times with anhydrous ethanol, and after filtering, place it in a 60°C forced air drying oven and dry it for 8h to obtain the modified silica.

[0042] The preparation steps of the temperature-resistant and salt-resistant polymer are as follows:

[0043] Step 3.1, weighing calculated amounts of acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, maleic anhydride and sodium p-styrenesulfonate in a molar ratio of 100:15:10:3 to mix the monomer components;

[0044] Step 3.2, weigh 8g of the monomer component, pour it into 100mL of deionized water, stir it at a stirring speed of 500r / min for 10min, then add a 30% mass fraction of sodium hydroxide aqueous solution to adjust the pH value to 7, then add 0.5g of modified silica and stir it at a stirring speed of 600r / min for 10min, the result is recorded as the mixture component, weigh 0.05g of ammonium persulfate and dissolve it in 10mL of deionized water, stir it at a stirring speed of 500r / min for 10min, the result is recorded as the initiator component;

[0045] Step 3.3, under nitrogen protection, drip the initiator component into the mixture component at a dripping rate of 1 drop / s, then react at a temperature of 65° C. for 5 hours, and the obtained temperature-resistant and salt-resistant polymer is obtained after freeze-drying.

[0046] Sulfonated styrene copolymers are prepared from styrene, maleic anhydride and benzoyl peroxide;

[0047] Wherein, the preparation steps of sulfonated styrene copolymer are:

[0048] Step 5.1, first mix toluene and acetone in an equal volume ratio and record it as a solvent component, then weigh styrene, maleic anhydride and benzoyl peroxide in a molar ratio of 1:1.2:1 and mix them as a raw material component, weigh 8g of the raw material component and disperse it in 100mL of the solvent component, stir at a stirring speed of 500r / min for 8min, then heat to 100℃ and react for 4h, cool to room temperature and filter to separate the solvent, and the result is recorded as a copolymer component;

[0049] Step 5.2, disperse the copolymer components in 50 mL of dichloroethane, heat to 25°C, and then add 0.2 g of sulfur trioxide at a drop rate of 1 drop / s under nitrogen protection. After reacting for 1 hour, add 20% sodium hydroxide aqueous solution by mass to adjust the pH value to 7. After separating the organic phase, place the aqueous phase in an oven at 60°C and dry it for 8 hours. Grind it through a 100-mesh sieve to obtain a sulfonated styrene copolymer.

[0050] The high temperature resistant liquid fluid loss additive is prepared from itaconic acid, acrylamide and 2-acrylamido-2-methylpropanesulfonic acid as raw materials;

[0051] The preparation steps of the high temperature resistant liquid fluid loss additive are as follows:

[0052] Step 7.1, weigh 4 g of itaconic acid and 20 g of deionized water into a flask, stir at a stirring speed of 300 r / min for 10 min in a water bath at 40° C., then add a calculated amount of acrylamide, 2-acrylamido-2-methylpropanesulfonic acid and 80 g of deionized water, and dropwise add a 30% mass fraction of sodium hydroxide aqueous solution to adjust the pH value to 9. The result is recorded as a monomer component, wherein the molar ratio of itaconic acid, acrylamide and 2-acrylamido-2-methylpropanesulfonic acid is 2:1:7;

[0053] Step 7.2, weigh 2g of silicon carbide powder and 2g of silane coupling agent KH-570 and add them to the monomer component, stir and react at a stirring speed of 500r / min in a water bath at 40°C for 15min, add 0.5g of ammonium persulfate and continue to react for 6h, and the result is a high temperature resistant liquid fluid loss reducer.

[0054] A preparation method of a composite oil well cement fluid loss reducer, the preparation method comprising:

[0055] 12 parts by weight of a heat-resistant and salt-resistant polymer and 10 parts by weight of a sulfonated styrene copolymer were weighed and poured into a ball mill for ball milling. After ball milling for 10 minutes, 1 part by weight of a silane coupling agent KH-560 and 15 parts by weight of a high-temperature resistant liquid fluid loss additive were added and ball milling was continued for 10 minutes to obtain a composite oil well cement fluid loss additive.

[0056] Example 2

[0057] The composite oil well cement fluid loss reducer of the present embodiment is composed of the following components: a temperature-resistant and salt-resistant polymer, a sulfonated styrene copolymer, a high temperature-resistant liquid fluid loss reducer, and a silane coupling agent KH-560.

[0058] The heat-resistant and salt-resistant polymer is prepared from modified silica, acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, maleic anhydride and sodium p-styrenesulfonate;

[0059] Wherein, the preparation steps of modified silicon dioxide are:

[0060] Step 2.1, weigh 2 g of silane coupling agent KH-570 and disperse it in 200 mL of 75% ethanol aqueous solution, disperse it ultrasonically at a frequency of 28 kHz for 30 min, then add anhydrous oxalic acid to adjust the pH value to 5, and the result is recorded as a modified solution;

[0061] Step 2.2, add 10g of nano-silica to the modified solution, ultrasonically disperse it at a frequency of 26kHz for 1.5h, and then condense and reflux it at a temperature of 60°C and a speed of 300r / min for 2.5h to obtain a gel product, wash the gel product 5 times with anhydrous ethanol, and after filtering, place it in a 60°C forced air drying oven and dry it for 8h to obtain the modified silica.

[0062] The preparation steps of the temperature-resistant and salt-resistant polymer are as follows:

[0063] Step 3.1, weighing calculated amounts of acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, maleic anhydride and sodium p-styrenesulfonate in a molar ratio of 100:15:10:3 to mix the monomer components;

[0064] Step 3.2, weigh 10g of the monomer component, pour it into 100mL of deionized water, stir it at a stirring speed of 500r / min for 10min, then add a 30% mass fraction of sodium hydroxide aqueous solution to adjust the pH value to 7, then add 1g of modified silica and stir it at a stirring speed of 600r / min for 10min, the result is recorded as the mixture component, weigh 0.1g of ammonium persulfate and dissolve it in 10mL of deionized water, stir it at a stirring speed of 500r / min for 10min, the result is recorded as the initiator component;

[0065] Step 3.3, under nitrogen protection, drip the initiator component into the mixture component at a dripping rate of 1 drop / s, then react at a temperature of 65° C. for 5 hours, and the obtained temperature-resistant and salt-resistant polymer is obtained after freeze-drying.

[0066] Sulfonated styrene copolymers are prepared from styrene, maleic anhydride and benzoyl peroxide;

[0067] Wherein, the preparation steps of sulfonated styrene copolymer are:

[0068] Step 5.1, firstly mix toluene and acetone in an equal volume ratio and record it as a solvent component, then weigh styrene, maleic anhydride and benzoyl peroxide in a molar ratio of 1:1.2:1 and mix them as a raw material component, weigh 10g of the raw material component and disperse it in 100mL of the solvent component, stir at a stirring speed of 500r / min for 8min, then heat to 100℃ and react for 4h, cool to room temperature and filter to separate the solvent, and the result is recorded as a copolymer component;

[0069] Step 5.2, disperse the copolymer components in 50 mL of dichloroethane, heat to 30°C, and then add 0.3 g of sulfur trioxide at a drop rate of 1 drop / s under nitrogen protection. After reacting for 2 hours, add 20% sodium hydroxide aqueous solution by mass to adjust the pH value to 7. After separating the organic phase, place the aqueous phase in an oven at 60°C and dry it for 8 hours. Grind it through a 100-mesh sieve to obtain a sulfonated styrene copolymer.

[0070] The high temperature resistant liquid fluid loss additive is prepared from itaconic acid, acrylamide and 2-acrylamido-2-methylpropanesulfonic acid as raw materials;

[0071] The preparation steps of the high temperature resistant liquid fluid loss additive are as follows:

[0072] Step 7.1, weigh 4 g of itaconic acid and 20 g of deionized water into a flask, stir at a stirring speed of 300 r / min for 10 min in a water bath at 50° C., then add a calculated amount of acrylamide, 2-acrylamido-2-methylpropanesulfonic acid and 80 g of deionized water, and dropwise add a 30% mass fraction of sodium hydroxide aqueous solution to adjust the pH value to 9. The result is recorded as a monomer component, wherein the molar ratio of itaconic acid, acrylamide and 2-acrylamido-2-methylpropanesulfonic acid is 2:1:7;

[0073] Step 7.2, weigh 2g of silicon carbide powder and 2g of silane coupling agent KH-570, add them to the monomer component, stir and react at a stirring speed of 500r / min in a water bath at 50°C for 30min, add 0.5g of ammonium persulfate and continue to react for 8h, and the result is a high temperature resistant liquid fluid loss reducer.

[0074] A preparation method of a composite oil well cement fluid loss reducer, the preparation method comprising:

[0075] Weigh 5 parts by weight of a heat-resistant and salt-resistant polymer and 12 parts by weight of a sulfonated styrene copolymer and pour them into a ball mill for ball milling. After ball milling for 10 minutes, add 2 parts by weight of a silane coupling agent KH-560 and 18 parts by weight of a high-temperature resistant liquid fluid loss reducer and continue ball milling for 10 minutes to obtain a composite oil well cement fluid loss reducer.

[0076] Example 3

[0077] The composite oil well cement fluid loss reducer of the present embodiment is composed of the following components: a temperature-resistant and salt-resistant polymer, a sulfonated styrene copolymer, a high temperature-resistant liquid fluid loss reducer, and a silane coupling agent KH-560.

[0078] The heat-resistant and salt-resistant polymer is prepared from modified silica, acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, maleic anhydride and sodium p-styrenesulfonate;

[0079] Wherein, the preparation steps of modified silicon dioxide are:

[0080] Step 2.1, weigh 2 g of silane coupling agent KH-570 and disperse it in 200 mL of 75% ethanol aqueous solution, disperse it ultrasonically at a frequency of 28 kHz for 30 min, then add anhydrous oxalic acid to adjust the pH value to 5, and the result is recorded as a modified solution;

[0081] Step 2.2, add 10g of nano-silica to the modified solution, ultrasonically disperse it at a frequency of 26kHz for 1.5h, and then condense and reflux it at a temperature of 60°C and a speed of 300r / min for 2.5h to obtain a gel product, wash the gel product 4 times with anhydrous ethanol, and after filtering, place it in a 60°C forced air drying oven and dry it for 8h to obtain the modified silica.

[0082] The preparation steps of the temperature-resistant and salt-resistant polymer are as follows:

[0083] Step 3.1, weighing calculated amounts of acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, maleic anhydride and sodium p-styrenesulfonate in a molar ratio of 100:15:10:3 to mix the monomer components;

[0084] Step 3.2, weigh 9g of the monomer component, pour it into 100mL of deionized water, stir it at a stirring speed of 500r / min for 10min, then add a 30% mass fraction of sodium hydroxide aqueous solution to adjust the pH value to 7, then add 0.8g of modified silica and stir it at a stirring speed of 600r / min for 10min, the result is recorded as the mixture component, weigh 0.08g of ammonium persulfate and dissolve it in 10mL of deionized water, stir it at a stirring speed of 500r / min for 10min, the result is recorded as the initiator component;

[0085] Step 3.3, under nitrogen protection, drip the initiator component into the mixture component at a dripping rate of 1 drop / s, then react at a temperature of 65° C. for 5 hours, and the obtained temperature-resistant and salt-resistant polymer is obtained after freeze-drying.

[0086] Sulfonated styrene copolymers are prepared from styrene, maleic anhydride and benzoyl peroxide;

[0087] Wherein, the preparation steps of sulfonated styrene copolymer are:

[0088] Step 5.1, first mix toluene and acetone in an equal volume ratio and record it as a solvent component, then weigh styrene, maleic anhydride and benzoyl peroxide in a molar ratio of 1:1.2:1 and mix them as a raw material component, weigh 9g of the raw material component and disperse it in 100mL of the solvent component, stir at a stirring speed of 500r / min for 8min, then heat to 100℃ and react for 4h, cool to room temperature and filter to separate the solvent, and the result is recorded as a copolymer component;

[0089] Step 5.2, disperse the copolymer components in 50 mL of dichloroethane, heat to 28°C, and then add 0.2 g of sulfur trioxide at a drop rate of 1 drop / s under nitrogen protection. After reacting for 2 hours, add 20% sodium hydroxide aqueous solution by mass to adjust the pH value to 7. After separating the organic phase, place the aqueous phase in an oven at 60°C and dry it for 8 hours. Grind it through a 100-mesh sieve to obtain a sulfonated styrene copolymer.

[0090] The high temperature resistant liquid fluid loss additive is prepared from itaconic acid, acrylamide and 2-acrylamido-2-methylpropanesulfonic acid as raw materials;

[0091] The preparation steps of the high temperature resistant liquid fluid loss additive are as follows:

[0092] Step 7.1, weigh 4 g of itaconic acid and 20 g of deionized water into a flask, stir at a stirring speed of 300 r / min for 10 min in a water bath at 45°C, then add a calculated amount of acrylamide, 2-acrylamido-2-methylpropanesulfonic acid and 80 g of deionized water, and dropwise add a 30% mass fraction of sodium hydroxide aqueous solution to adjust the pH value to 9. The result is recorded as a monomer component, wherein the molar ratio of itaconic acid, acrylamide and 2-acrylamido-2-methylpropanesulfonic acid is 2:1:7;

[0093] Step 7.2, weigh 2g of silicon carbide powder and 2g of silane coupling agent KH-570 and add them to the monomer component, stir and react at a stirring speed of 500r / min in a water bath at 45°C for 22min, add 0.5g of ammonium persulfate and continue to react for 7h, and the result is a high temperature resistant liquid fluid loss reducer.

[0094] A preparation method of a composite oil well cement fluid loss reducer, the preparation method comprising:

[0095] 13 parts by weight of a heat-resistant and salt-resistant polymer and 11 parts by weight of a sulfonated styrene copolymer were weighed and poured into a ball mill for ball milling. After ball milling for 10 minutes, 2 parts by weight of a silane coupling agent KH-560 and 17 parts by weight of a high-temperature resistant liquid fluid loss additive were added and ball milling was continued for 10 minutes to obtain a composite oil well cement fluid loss additive.

[0096] Comparative Example 1

[0097] The composite oil well cement fluid loss reducer and its preparation method provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 1, the temperature-resistant and salt-resistant polymer in Example 1 is replaced with a sulfonated styrene copolymer.

[0098] Comparative Example 2

[0099] The composite oil well cement fluid loss reducer and its preparation method provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 1, the sulfonated styrene copolymer in Example 1 is replaced with a temperature-resistant and salt-resistant polymer.

[0100] Performance Testing

[0101] The composite oil well cement fluid loss reducers prepared in Examples 1-3 and Comparative Examples 1-2 are marked as Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2, respectively. Then, the performance of Examples 1-3 and Comparative Examples 1-2 is tested. The specific testing method is as follows:

[0102] Prepare cement slurry in accordance with "GB / T19139-2012 Test Method for Oil Well Cement", and test the API water loss, salt resistance and high temperature resistance of cement slurry in accordance with "SY / T5504.4-2008 Evaluation Method for Oil Well Cement Admixtures" and "SY / T6544-2017 Performance Requirements for Oil Well Cement Slurry".

[0103] 1. During the API water loss test, the cement slurry formula is: 54% oil well cement + 1% compound oil well cement fluid loss reducer + 0.5% dispersant + 0.5% retarder + 44% water;

[0104] 2. In the process of testing salt resistance, the formula of cement slurry is: 54% oil well cement + 1% compound oil well cement fluid loss reducer + 0.5% dispersant + 0.5% retarder + 44% water, where the water includes 20% sodium chloride by mass. The salt resistance is expressed by the API water loss under salt conditions;

[0105] 3. In the process of testing the high temperature resistance, the formula of the cement slurry is: 54% oil well cement + 1% compound oil well cement fluid loss reducer + 0.5% dispersant + 0.5% retarder + 44% water. The high temperature resistance of the fluid loss reducer is indicated by the length of thickening time at different high temperatures.

[0106]

[0107] It can be seen from the data in the above table that the cement slurry added with the composite oil well cement fluid loss reducer in Examples 1-3 has a lower API water loss than that in Comparative Examples 1-2, and the API water loss changes less under salt conditions, indicating that the composite oil well cement fluid loss reducer in the present invention has better salt resistance; secondly, the cement slurry added with the composite oil well cement fluid loss reducer in Examples 1-3 has a longer thickening time under high temperature conditions than that in Comparative Examples 1-2, indicating that the composite oil well cement fluid loss reducer in the present invention has better high temperature resistance.

[0108] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0109] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A composite oil well cement fluid loss reducer, characterized in that: The composite oil well cement fluid loss reducer is composed of the following components: a temperature-resistant and salt-resistant polymer, a sulfonated styrene copolymer, a high-temperature-resistant liquid fluid loss reducer, and a silane coupling agent KH-560; The temperature-resistant and salt-resistant polymer is prepared with modified silicon dioxide, acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, maleic anhydride and sodium p-styrenesulfonate as raw materials; The sulfonated styrene copolymer is prepared using styrene, maleic anhydride and benzoyl peroxide as raw materials; The high temperature resistant liquid fluid loss additive is prepared from itaconic acid, acrylamide and 2-acrylamido-2-methylpropanesulfonic acid as raw materials.

2. The composite oil well cement fluid loss reducer according to claim 1, characterized in that: The preparation steps of the modified silicon dioxide are: Step 2.1, weigh 2 g of silane coupling agent KH-570 and disperse it in 200 mL of 75% ethanol aqueous solution, disperse it ultrasonically at a frequency of 28 kHz for 30 min, then add anhydrous oxalic acid to adjust the pH value to 5, and the result is recorded as a modified solution; Step 2.2, add 10g of nano-silica to the modified solution, ultrasonically disperse it at a frequency of 26kHz for 1.5h, and then condense and reflux it at a temperature of 60°C and a speed of 300r / min for 2.5h to obtain a gel product, wash the gel product with anhydrous ethanol for 3-5 times, filter it, and dry it in a 60°C forced air drying oven for 8h to obtain the modified silica.

3. The composite oil well cement fluid loss reducer according to claim 1, characterized in that: The preparation steps of the temperature-resistant and salt-resistant polymer are as follows: Step 3.1, weighing calculated amounts of acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, maleic anhydride and sodium p-styrenesulfonate in a molar ratio of 100:15:10:3 to mix the monomer components; Step 3.2, weigh 8-10g of the monomer component, pour it into 100mL of deionized water and disperse it evenly, then add sodium hydroxide aqueous solution to adjust the pH value to 7, then add 0.5-1g of modified silica and mix evenly, the result is recorded as the mixture component, weigh 0.05-0.1g of ammonium persulfate and dissolve it in 10mL of deionized water, and the result after it is fully dissolved is recorded as the initiator component; Step 3.3, under nitrogen protection, drip the initiator component into the mixture component, then react at 65° C. for 5 hours, and freeze-dry to obtain a temperature-resistant and salt-resistant polymer.

4. The composite oil well cement fluid loss reducer according to claim 3, characterized in that: In step 3.2, the specific operation for uniform dispersion is stirring at a stirring speed of 500 r / min for 10 min, the mass fraction of the sodium hydroxide aqueous solution is 30%, the specific operation for uniform mixing is stirring at a stirring speed of 600 r / min for 10 min, the specific operation for sufficient dissolution is stirring at a stirring speed of 500 r / min for 10 min, and the dripping rate in step 3.3 is 1 drop / s.

5. The composite oil well cement fluid loss reducer according to claim 1, characterized in that: The preparation steps of the sulfonated styrene copolymer are: Step 5.1, first mix toluene and acetone in an equal volume ratio and record it as a solvent component, then weigh styrene, maleic anhydride and benzoyl peroxide in a molar ratio of 1:1.2:1 and mix them as a raw material component, weigh 8-10g of the raw material component and disperse it in 100mL of the solvent component, stir it evenly, heat it to 100℃ and react it for 4h, cool it to room temperature and filter out the solvent, and the result is recorded as a copolymer component; Step 5.2, disperse the copolymer components in 50 mL of dichloroethane, heat to 25-30°C, and then add 0.2-0.3 g of sulfur trioxide under nitrogen protection. After reacting for 1-2 hours, add sodium hydroxide aqueous solution to adjust the pH value to 7. After separating the organic phase, place the aqueous phase in an oven at 60°C and dry it for 8 hours. Grind it through a 100-mesh sieve to obtain a sulfonated styrene copolymer.

6. The composite oil well cement fluid loss reducer according to claim 5, characterized in that: In step 5.1, the specific operation of stirring uniformly is stirring at a stirring speed of 500 r / min for 8 minutes. In step 5.2, the dripping rate is 1 drop / s, and the mass fraction of the sodium hydroxide aqueous solution is 20%.

7. The composite oil well cement fluid loss reducer according to claim 1, characterized in that: The preparation steps of the high temperature resistant liquid fluid loss additive are as follows: Step 7.1, weigh 4 g of itaconic acid and 20 g of deionized water into a flask, stir in a water bath at 40-50° C. until completely dissolved, then add a calculated amount of acrylamide, 2-acrylamido-2-methylpropanesulfonic acid and 80 g of deionized water, dropwise add an aqueous sodium hydroxide solution to adjust the pH value to 9, and the result is recorded as a monomer component, wherein the molar ratio of itaconic acid, acrylamide and 2-acrylamido-2-methylpropanesulfonic acid is 2:1:7; Step 7.2, weigh 2g of silicon carbide powder and 2g of silane coupling agent KH-570, add them to the monomer component, stir and react for 15-30min in a water bath at 40-50°C, add 0.5g of ammonium persulfate and continue to react for 6-8h, and the result is a high temperature resistant liquid fluid loss reducer.

8. The composite oil well cement fluid loss reducer according to claim 7, characterized in that: In step 7.1, the specific operation of stirring until complete dissolution is stirring at a stirring speed of 300 r / min for 10 min, and the mass fraction of the sodium hydroxide aqueous solution is 30%. In step 7.2, the stirring speed of the stirring reaction is 500 r / min.

9. The method for preparing a composite oil well cement fluid loss reducer according to any one of claims 1 to 8, characterized in that: The preparation method is: 12-15 parts by weight of a heat-resistant and salt-resistant polymer and 10-12 parts by weight of a sulfonated styrene copolymer are weighed and poured into a ball mill for ball milling. After ball milling for 10 minutes, 1-2 parts by weight of a silane coupling agent KH-560 and 15-18 parts by weight of a high-temperature resistant liquid fluid loss additive are added and ball milling is continued for 10 minutes to obtain a composite oil well cement fluid loss additive.